Pengaruh Whistleblowing Systems dengan Dimensi Fraud Hexagon di Perusahaan BUMN Non Perbankan - Trie Sartika Pratiwi; Sri Maryati; Abdul Rohman (Strategi : Jurnal Manajemen, 2026)
This study aims to examine the influence of financial stability, whistleblowing system, related party transaction, director change, frequent number of CEO’s pictures, and political connection on financial reporting fraud. The population used in this study is non-banking State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) for the period 2018 – 2022. Penentuan sampel menggunakan teknik purposive sampling yang menghasilkan jumlah sampel sebanyak 18 perusahaan. The analysis technique used in this study is multiple linear regression analysis using IBM SPSS software. The findings of the study indicate that: (1) financial stability has a positive and significant effect on financial reporting fraud; (2) the whistleblowing system has a positive and significant effect on financial reporting fraud; (3) related party transactions have a positive and significant effect on financial reporting fraud; (4) director change does not have a significant effect on financial reporting fraud; (5) frequent number of CEO's pictures does not have a significant effect on financial reporting fraud; and (6) political connections do not have a significant effect on financial reporting fraud. Abstrak : Penelitian ini bertujuan untuk menguji pengaruh financial stability, whistleblowing system, related party transaction, director change, frequent number of CEO’s pictures, dan political connection terhadap kecurangan laporan keuangan. Populasi yang digunakan dalam penelitian ini adalah perusahaan Badan Usaha Milik Negara (BUMN) non perbankan yang terdaftar di Bursa Efek Indonesia (BEI) periode tahun 2018 – 2022. Penentuan sampel menggunakan teknik purposive sampling yang menghasilkan jumlah sampel sebanyak 18 perusahaan. Teknik analisis yang digunakan dalam penelitian ini adalah analisis regresi liniear berganda dengan menggunakan software IBM SPSS. Hasil temuan dalam penelitian menunjukkan bahwa: (1) financial stability berpengaruh positif dan signifikan terhadap kecurangan laporan keuangan; (2) whistleblowing system berpengaruh positif dan signifikan terhadap kecurangan laporan keuangan; (3) related party transaction berpengaruh positif dan signifikan terhadap kecurangan laporan keuangan; (4) director change tidak berpengaruh secara signifikan terhadap kecurangan laporan keuangan; (5) frequent number of CEO’s pictures tidak berpengaruh secara signifikan terhadap kecurangan laporan keuangan; dan (6) political connection tidak berpengaruh secara signifikan terhadap kecurangan laporan keuangan.